1977
DOI: 10.1083/jcb.73.2.366
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and axonal transport of rat neurohypophysial proteins and peptides.

Abstract: ~S-cysteine injected adjacent to the supraoptic nucleus (SON) of the rat is rapidly incorporated into proteins. These 35S-cysteine-labeled proteins in the SON (1-24 h after injection) were separated by polyacrylamide gel electrophoresis, and the distribution of radioactive proteins on the gels was analyzed. 1 h after injection, about 73% of the radioactivity appeared in two peaks (both about 20,000 mol wt). With time, these peaks (putative precursors of neurophysin) decreased, as a 12,000 mol wt peak (containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
110
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 278 publications
(117 citation statements)
references
References 40 publications
(47 reference statements)
7
110
0
Order By: Relevance
“…Sachs and his colleagues (4)(5)(6)(7)(8) have hypothesized that vasopressin and its neurophysin come from a common precursor protein that is synthesized in the hypothalamus by a ribosomal mechanism. We have already presented some evidence consistent with this hypothesis (9,10 sopressin and its associated neurophysin (11,12) and hence have diabetes insipidus-to determine which of the putative precursors, intermediates, and neurophysins are related to vasopressin and which to oxytocin. MATERIALS AND METHODS Animals and Operative Procedures.…”
mentioning
confidence: 51%
“…Sachs and his colleagues (4)(5)(6)(7)(8) have hypothesized that vasopressin and its neurophysin come from a common precursor protein that is synthesized in the hypothalamus by a ribosomal mechanism. We have already presented some evidence consistent with this hypothesis (9,10 sopressin and its associated neurophysin (11,12) and hence have diabetes insipidus-to determine which of the putative precursors, intermediates, and neurophysins are related to vasopressin and which to oxytocin. MATERIALS AND METHODS Animals and Operative Procedures.…”
mentioning
confidence: 51%
“…In addition, the synthesis of another peptide with endorphin-like immuno- The immunoprecipitated peaks are illustrated in Figs. [1][2][3]. RF represents the mobility of each peak on acid/urea gels relative to cytochrome c. Mr was determined by elution of peaks from acid/urea gels and subsequent electrophoresis on NaDodSO4 gels and by direct application of immunoprecipitates to NaDodSO4 gels and correlation of the peaks with the acid/urea gel profile of the same aliquot.…”
Section: Resultsmentioning
confidence: 99%
“…Vasopressin is synthesized in the magnocellular neurons of the supraoptic and paraventricular nuclei of the hypothalamus and transported to the posterior pituitary via microtubules (15). Colchicine is well known to disrupt microtubular transport and we recently reported that low doses of colchicine injected into the third ventricle of the hypothalamus of rats blocked transport of vasopressin while synthesis continued (16 7 ,ug, was injected in 1 M1 0.15 M NaCl at a rate of 0.1 l every 10 s. After injection, the hole in the skull was sealed with bone wax (Ethicon, Somerville, NJ), the skin was closed with clips, and the animals were kept warm until they recovered from anesthesia when they were returned to their cages.…”
Section: Methodsmentioning
confidence: 99%